Cardiac Gunshot Injury: A Serendipitous Miss! - Jain, Jeetesh (JACC Case Rep, 2020)
Penetrating cardiac injuries carry a grave prognosis. We present a rare case of thoracic gunshot injury where the bullet ricocheted and lodged in the pericardium without causing damage to the adjacent cardiac structures. Multimodality imaging helped in localizing the bullet, assessing damage, and planning safe surgical removal without cardiopulmonary bypass. (Level of Difficulty: Beginner.)